THE INFLUENCE OF TRUST AND HEDONIC MOTIVATION IN INSTAGRAM STORIES TO ENHANCE CONSUMER PURCHASE INTENTION OF DEAR ME BEAUTY LIPSTICK PRODUCT (STUDY CASE AMONG FEMALE INSTAGRAM USERS IN PONTIANAK) - Ningtias, Fiola Okta Ningtias B1024151003 (Jurnal Manajemen Update, 2020)
This study aims to examine and analyze the influence of trust and hedonic motivation in Instagram stories to enhance consumer purchase intention of Dear Me Beauty Lipstick Product This work uses a quantitative approach to the study of data using multiple linear regression approaches. This research conducted using online questionnaire that spread using google form. The participants in this analysis are women aged 20 to > 25 years old. The findings of this study are that Hedonic Motivation, Instagram Stories Features and Trust have a significant positive effect on Consumer Purchase Intention. The findings of the analysis showed that the three independent variables had a major positive effect. Hedonic Motivation, Instagram Stories Features and Trust have a major positive impact on Purchase Intention at a 5% point of significance.Kotler, P. A. (2006). Principles of Marketing theEuropean Edition. Great Britain. Prentice Hall.Kover A.J., G. S. (1995). Creativity versus effectiveness. Journal of Advertising Research.Shapiro, S. &. (2001). Memory-based measures for assessing advertising effects: a comparison of explicit and implicit memory effects. journal of Advertising.Shimp, T. (2000). Periklanan Promosi: Aspek Tambahan Komunikasi Pemasaran Terpadu,.Till, B. a. (2005). Recall and persuasuion: Does creative advertising matter? Journal Traffic of advertising.Wang, J. C. (2013). Effect of Celebrity Endorsements on Consumer Purchase Intentions: Advertising Effect and Advertising Appeal as Mediators: Human Factors and Ergonomics in Manufacturing & Service Industries.Wua, P. C.-Y.-R. (2011). The effect of store image and service quality on brand image and purchase intention for private label brands. Australasian Marketing Journal.Swastha, B. &. (2002). Modern Marketing Management.Wua, P. C.-Y.-R. (2011). The effect of store image and service quality on brand image and purchase intention for private label brands. Australasian Marketing Journal.Malhotra, N. K. (2010). Marketing Reseach: An Applied Orientation Sixth Edition Pearson Education.Engel M, e. a. (1994). Phosphorylation of nm23/nucleoside diphosphate kinase by casein kinase. Biochem Biophys Res Commun.